Community nature and Primary Health Care: Environmental education as a strategy for social transformation (Research, Society and Development, 2021)
This study aimed to understand how the discourse of the health / environment relationship is constituted in the training of nurses based on the community nature. This is a qualitative study with a materialistic approach, carried out with seven universities located in the south of Brazil. The collection was carried out based on the speeches described in the contents of the following institutional documents available on the pages of the selected universities. Three categories were held: Community / social nature and training of human resources for the Unified Health System in capitalist society, Community Health and Health Promotion: focus of Primary Health Care and Training strategies for social transformation: popular participation and sustainability towards awareness. Thus, it can be concluded that there is a need for discussion and expansion of spaces for academic and professional training in health courses about the health / environment relationship, through the community nature.